Calmatic headphone / Rohaiza Kamis … [et al.] - Kamis, Rohaiza; Ibrahim, Siti Nurul Huda; Mohd Hatta, Nurul Ashiqin; Mohd Asyraf, Nurshafika; Yaacob, Nurul Atikah; Maznan, Muhammad Khairun Na'im; Baharuddin, Norshahira (Division of Research and Industry Linkages, 2017)
Autism, or autism spectrum disorder refers to a range of condition characterized by challenges with social skills, repetitive behaviors, speech and nonverbal communication, as well as by unique strengths and differences, in Malaysia, the number of autistic is very relatively small but all the autistic is consider as special case. This research shows that role played by the parent give high impact towards the safety of their special children. They have to put high priority to the movement of their children since we cannot predict their next movement. This innovation and improvement of the product can less the burden that the parent need to bring. In addition, the innovation is expected to have positive impact towards the attitude of the autistic.